Determinants delaying the early detection of diabetic retinopathy : Suggested nursing instructions - Asmaa Mustafa Khalifa; Amel Gomaa Abdelnaby; Enace Mohamed Abdelaal; Nagat Elmorsy Ibrahim (Cairo : Asmaa Mustafa Khalifa, 2020)
Regular eye examinations help in early detection and enhance timely treatment for diabetic retinopathy (DR) .Aim of the present study was to identify Determinants Delaying the Early Detection of Diabetic Retinopathy: Suggested Nursing Instructions Abstract Regular eye examinations help in early detection and enhance timely treatment for diabetic retinopathy (DR). Aim of the present study was to identify determinants delaying the early detection of diabetic retinopathy and develop suggested nursing instructions. Design: Descriptive exploratory design was utilized. Setting: The study was conducted in ophthalmology outpatient clinic at Sohag University Hospital. Sample: Convenient sample of 120 adult male and female patients diagnosed with diabetic retinopathy was included as a study sample. Data collection tools: Two tools were used in data collection, the first tool: Structured Interview Questionnaire for demographic and medical data and the second tool: Diabetic Retinopathy Determinants Assessment Form. Results: The main findings revealed that nearly three quarters of patients age ranged from 50 < 60 years, less than half of study sample can{u2019}t read and write, half of them had family income <1000 L.E, 70% of the study sample didn't go for regular eye checkup after diagnosis of diabetes, regarding the most prominent determinants delaying early detection of DR: nearly three quarters of patients' had unsatisfactory knowledge; salary is only covering basic life, commitment to another financial priority, lack of escort and time and health care providers didn't mention diabetes complications on the eye
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Surgical Nursing
Issued also as CD
Keywords: Delaying; Detection; Determinants